Large schwannoma of the median nerve at the distal forearm - Vulović, Dejan; Kozarski, Jefta; Vulović, Tatjana; Spasić, Marko; Šarenac Vulović, Tatjana; Ahmed T. Mubarak, Tahir; Stanković, Vesna; Al-Shraim, Mubarak; Rakić, Dejana (Vojnosanitetski pregled, 2023)
Introduction. Schwannoma, also known as neurilemmoma, is a rare but one of the most common tumors of the peripheral nerves. It originates from Schwann cells of the peripheral nerve sheaths. Schwannoma mostly occurs in adults between 20 to 70 years of age. The regions where the tumor most commonly occurs are the head and neck, but it can occur almost anywhere in the body or the organs. Schwannomas are usually up to 2.5 cm in size but may grow to 4–5 cm. In this study, the rare case of large schwannoma of the median nerve in the distal part of the forearm is presented. Case report. A 46-year-old male patient was referred to a plastic surgeon with a diagnosis of lipoma on the anterior side of the distal third of the left forearm. Ultrasound and magnetic resonance imaging were done, and the surgery was performed after that. An encapsulated tumor of the median nerve was found, and the tumor was completely removed without nerve damage. Histological analysis showed a benign schwannoma of cellular type and biphasic shape. In the postoperative course, there was transient paresthesia. One year after surgery, no tumor recurrence nor neurological deficit was recorded. Conclusion. Schwannoma is the most common benign tumor of peripheral nerves. Schwannomas over 5 cm in size are extremely rare. Appropriate physical examination, preoperative imaging studies, and histological verification are required for the final diagnosis. The method of choice in treating large schwannomas is complete surgical excision.